2022
DOI: 10.1111/jocd.14792
|View full text |Cite
|
Sign up to set email alerts
|

GNLY gene polymorphism: A potential role in understanding psoriasis pathogenesis

Abstract: Background Psoriasis is a chronic inflammatory illness that affects 2%–3% of the world's population. Granulysin (GNLY), along with granzyme and perforin, is a cytolytic antimicrobial peptide (AMP) released from the granules of both natural killer (NK) cells and cytotoxic T lymphocytes (CTLs). By immunohistochemistry, it has been shown that GNLY expression increases in psoriasis lesions. Aims Our work aimed to reveal the potential effect of GNLY gene polymorphism and its association with psoriasis pathogenesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Granulysin (GNLY) is a cytotoxic granule that is cosecreted with granzyme and perforin from the granules of human cytotoxic T lymphocytes (CTLs) and natural killer (NK) cells. It has been documented to possess diverse antimicrobial properties [33,34]. GNLY is predominantly expressed in human CTLs and NK cells and has been implicated in a plethora of pathological conditions, including infections, cancer, transplantation, and dermatological disorders [35].…”
Section: Discussionmentioning
confidence: 99%
“…Granulysin (GNLY) is a cytotoxic granule that is cosecreted with granzyme and perforin from the granules of human cytotoxic T lymphocytes (CTLs) and natural killer (NK) cells. It has been documented to possess diverse antimicrobial properties [33,34]. GNLY is predominantly expressed in human CTLs and NK cells and has been implicated in a plethora of pathological conditions, including infections, cancer, transplantation, and dermatological disorders [35].…”
Section: Discussionmentioning
confidence: 99%
“…As GNLY is not present in rodents, it is unfortunate that we did not further validate its expression in our mice model. But GNLY has been found to play an important role in infection and immune-related diseases, such as osteoarthritis, psoriasis and chronic viral hepatitis [31][32][33] . Currently, human GNLY gene has been constructed into transgenic mice models and effectively used in experimental investigations.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with our study. GNLY is a cytolytic antimicrobial peptide (AMP) released from the granules of both cytotoxic T lymphocytes (CTLs) and natural killer (NK) cells, which mainly involved in the occurrence of psoriasis [ 42 ]. Zhang Q found that the hub genes GNLY may be associated with the prognosis of sepsis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%